PROBLEMS AND SPECIFIC FEATURES OF GENDER EQUALITY IN OLYMPIC AND PROFESSIONAL SPORTS (Physical Culture and Sport: Scientific Perspective, 2025)
In today's society, sport is not only a component of human physical development but also a powerful social tool that shapes values, norms, and behavioral patterns. At the same time, despite the proclaimed principles of equality and non-discrimination, gender inequality remains a persistent challenge at both the national and international levels of the sports environment. The study analyzes the current challenges and peculiarities of the development of Olympic and professional sports in the context of globalization, professionalization, and socio-cultural changes. The author emphasizes the need for a comprehensive approach to the study of sport as a social, economic, and cultural phenomenon. Particular attention is paid to gender equality in sport. The author reveals the impact of gender differences on the psychological and physical training of athletes; gender discrimination in professional sports, including inequality in representation, sexism, problems of sports language and media coverage; women's experience in sports management, including barriers to career growth and strategies for overcoming discrimination; differences between the concepts of ‘sex’ and ‘gender’ in the sports context. In general, the author emphasizes the need to transform the sports culture, develop a gender-sensitive approach, and implement systemic changes to ensure equality in Olympic and professional sports. The purpose of the article is to study and discuss the problem and peculiarities of gender equality in Olympic and professional sports.The analytical study and discussion of the problem and peculiarities of gender equality in Olympic and professional sports allow us to draw the following conclusions. In particular, the relevance of the problem of gender equality in Olympic and professional sports is beyond doubt. Despite progressive changes and positive trends in recent years, gender inequality remains a systemic problem at the global level. The key issues are centered around women's limited access to certain sports, unequal pay, insufficient media coverage, low representation of women in governing bodies, and the persistence of stereotypes and sexism in the professional environment. Professional sports demonstrate a particular acuteness of the problems of financial and media inequality, which are related to market mechanisms that have not yet been significantly adapted to the principles of gender equality.Olympic sport, although it has a more structured approach to gender balance (thanks to IOC policies), still faces challenges ranging from the participation of transgender athletes to the deep-seated impact of cultural barriers.
Keywords: olympic and professional sports; research; gender equality